Improving the safety of cell therapy with the TK-suicide gene - Greco, Raffaella; Oliveira, Giacomo; Stanghellini, Maria Teresa Lupo; Vago, Luca; Bondanza, Attilio; Peccatori, Jacopo; Cieri, Nicoletta; Marktel, Sarah; Mastaglio, Sara; Bordignon, Claudio; Bonini, Chiara; Ciceri, Fabio (Frontiers in Pharmacology, 2015)
While opening new frontiers for the cure of malignant and non-malignant diseases, the increasing use of cell therapy poses also several new challenges related to the safety of a living drug. The most effective and consolidated cell therapy approach is allogeneic haematopoietic stem cell transplantation (HSCT), the only cure for several patients with high-risk haematological malignancies. The potential of allogeneic HSCT is strictly dependent on the donor immune system, particularly on alloreactive T lymphocytes, that promote the beneficial graft-versus-tumour effect (GvT), but may also trigger the detrimental graft-versus-host-disease (GvHD). Gene transfer technologies allow to manipulate donor T cells to enforce GvT and foster immune reconstitution, while avoiding or controlling GvHD. The suicide gene approach is based on the transfer of a suicide gene into donor lymphocytes, for a safe infusion of a wide T cell repertoire, that might be selectively controlled in vivo in case of GvHD. The herpes simplex virus thymidine kinase (HSV-TK) is the suicide gene most extensively tested in humans. Expression of HSV-TK in donor lymphocytes confers lethal sensitivity to the anti-herpes drug, ganciclovir. Progressive improvements in suicide genes, vector technology and transduction protocols have allowed to overcome the toxicity of GvHD while preserving the antitumor efficacy of allogeneic HSCT. Several phase I-II clinical trials in the last 20 years document the safety and the efficacy of HSV-TK approach, able to maintain its clear value over the last decades, in the rapidly progressing horizon of cancer cellular therapy.